(untitled) - Novak, Andrej; Kazda, Antonin (Doprava a spoje, 2005)
This paper presents Automatic Dependent Surveillance is radically new technology that is redefining the paradigm of COMMUNICATIONS - NAVIGATION - SURVEILLANCE in Air Traffic Management today. Already proven as a viable low cost replacement for conventional radar, ADS allows pilots and air traffic controllers to "see" and control aircraft with more precision, and over a far larger percentage of the earth's surface, than has ever been possible before.